SURGICAL TREATMENT OF MAXILLARY FRACTURES: APPROACHES BASED ON LE FORT CLASSIFICATIONS AND THEIR CLINICAL IMPLICATIONS (International Seven Journal of Multidisciplinary, 2025)
Maxillary fractures are complex injuries with great functional and aesthetic impact, often caused by high-energy traumas, such as traffic accidents and assaults. The surgical treatment of these fractures has evolved considerably over time, with the advancement of rigid internal fixation techniques, which offer greater precision and lower morbidity compared to conventional methods. The Le Fort classification, proposed in 1901, remains a crucial tool for the diagnosis and surgical planning of these fractures, dividing them into three distinct types, which require different approaches. Le Fort I involves horizontal fractures, while Le Fort II and III are more complex, affecting the maxilla, nasal bones, and orbital structures. Early treatment with open reduction and rigid fixation has shown better clinical results, with a lower risk of long-term complications. In addition, the use of advanced technologies, such as CT scans and 3D models, has improved the planning and execution of surgeries, contributing to the faster and more efficient recovery of patients. This article reviews surgical approaches based on Le Fort's classifications, discussing their clinical implications in the management of maxillary fractures.